CD16 CAR-T cells enhance antitumor activity of CpG ODN-loaded nanoparticle-adjuvanted tumor antigen-derived vaccinevia ADCC approach - Xiaofei Zhang; Qin Hu; Xuesong He; Xinyue Cui; Zhaoyuan Liang; Li Wang; Xiongwei Deng; Ze Zhang; Wang Sheng; Xiaodong D. Han (Journal of Nanobiotechnology, 2023)
Abstract Background Combinatorial immunotherapy strategies for enhancing the responsiveness of immune system have shown great promise for cancer therapy. Engineered nanoformulation incorporated toll-like receptor (TLR) 9 agonist CpG ODN has shown more positive results in suppressing tumor growth and can significantly enhance other immunotherapy activity with combinatorial effects due to the innate and adaptive immunostimulatory effects of CpG. Results In the present work, protamine sulfate (PS) and carboxymethyl β-glucan (CMG) were used as nanomaterials to form nanoparticles through a self-assembly approach for CpG ODN encapsulation to generate CpG ODN-loaded nano-adjuvant (CNPs), which was subsequently mixed with the mixture of mouse melanoma-derived antigens of tumor cell lysates (TCL) and neoantigens to develop vaccine for anti-tumor immunotherapy. The obtained results showed that CNPs was able to effectively deliver CpG ODN into murine bone marrow-derived dendritic cells (DC) in vitro, and remarkably stimulate the maturation of DC cells with proinflammatory cytokine secretion. In addition, in vivo analysis showed that CNPs enhanced anti-tumor activity of PD1 antibody and CNPs-adjuvanted vaccine based on the mixture antigens of melanoma TCL and melanoma-specific neoantigen could not only induce anti-melanoma cellular immune responses, but also elicit melanoma specific humoral immune responses, which significantly inhibited xenograft tumor growth. Furthermore, CD16 CAR-T cells were generated by expressing CD16-CAR in CD3+CD8+ murine T cells. Conclusion Our results eventually showed that anti-melanoma antibodies induced by CNPs-adjuvanted TCL vaccines were able to collaborate with CD16-CAR-T cells to generate an enhanced targeted anti-tumor effects through ADCC (antibody dependent cell cytotoxicity) approach. CD16 CAR-T cells has thus a great potential to be an universal promising strategy targeting on solid tumor synergistic immunotherapy via co-operation with TCL-based vaccine.